2012
DOI: 10.1177/0363546512457648
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Demineralized Bone Matrix on Tendon-Bone Healing in an Intra-articular Rodent Model

Abstract: Introduction of osteoinductive DBM at the tendon-bone interface during ACL reconstructive surgery may improve short-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…Evidence from literature suggests that different BMPs found in demineralised bone result in differentiation of the MSCs into osteogenic, chondrogenic and tenogenic lineage [16, 17]. Rodeo and colleagues investigated the role of BMP-2 in tendon bone healing and concluded that BMP-2 enhances this healing and results in stronger tendon-bone attachment [1820]. Similar findings were also found by other research groups [2124].…”
Section: Introductionsupporting
confidence: 56%
“…Evidence from literature suggests that different BMPs found in demineralised bone result in differentiation of the MSCs into osteogenic, chondrogenic and tenogenic lineage [16, 17]. Rodeo and colleagues investigated the role of BMP-2 in tendon bone healing and concluded that BMP-2 enhances this healing and results in stronger tendon-bone attachment [1820]. Similar findings were also found by other research groups [2124].…”
Section: Introductionsupporting
confidence: 56%
“…A unilateral rat ACL reconstruction model was adopted as described previously [41] and slightly modified [50]. The surgical procedure was performed under strictly aseptic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…). In order to promote graft osseointegration, various methods had been engaged to reduce the fibrous scar tissue and enhance new bone formation at the graft‐bone interface …”
Section: Graft Healing Process After Implantationmentioning
confidence: 99%
“…In order to promote graft osseointegration, various methods had been engaged to reduce the fibrous scar tissue and enhance new bone formation at the graft-bone interface. 23,24 In addition, the graft ligamentization process of the intra-articular part consists of four phases: (1) inflammation, (2) revascularization, (3) cellular repopulation and resynovialization, and (4) remodeling. 25,26 The inserted graft is initially avascular without a synovial surface after ACL reconstruction.…”
Section: Graft Healing Process After Implantationmentioning
confidence: 99%